Digital Transformation and Green Credit: Strategic Implications for Bank Profitability - Grecia Alvionita Simanjorang; Febria Nalurita; Farah Margaretha Leon (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study seeks to examine the impact of non-performing loans, the loan-to-deposit ratio, green credit, and digitalisation on the profitability of Indonesia's banking system, while considering bank size and bank age as control factors. This research is distinctive due to its incorporation of green credit and digitalisation in response to the increasing significance of sustainability and technical advancement in the financial sector. This study utilises secondary data obtained from the annual reports of banking firms listed on the Indonesia Stock Exchange (IDX) for the years 2019 to 2024. The sample was chosen by a purposive sampling technique. The investigation utilised imbalanced panel data regression with a fixed effects model, leveraging EViews 9 software. The findings demonstrate that non-performing loans adversely and significantly impact profitability, while the loan-to-deposit ratio positively and significantly influences profitability. Additionally, green credit exerts a positive and significant effect on profitability, and both bank size and bank age as control variables significantly affect profitability. In contrast, digitalisation exerts no substantial influence on profitability. The findings underscore the necessity for banks to adeptly manage credit risk and optimise digital transformation to improve financial performance, alongside the vital role of government in fostering and developing green credit programs.